Competence Analysis of Islamic Religious Counselors at the Office of the Ministry of Religion in Kapuas Regency - Abdul Hamid; Irawanto; Riky Welly Saputra; Mukhlan Khairiry; Septeria Noor Yuliannisa (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to: 1) Analyze the Competence of Islamic Religious Instructors at the Office of the Ministry of Islamic Religion in Kapuas Regency, 2) Know the Efforts to Increase the Competence of Islamic Religious Instructors, 3) Analyze the supporting factors and inhibiting factors of the Competence of Islamic Religious Instructors in the Office of the Ministry of Religion of Kapuas Regency. The research was conducted with a qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation involving the State Civil Apparatus of the Office of the Ministry of Religion of Kapuas Regency, who served as Islamic Religious Extension (inform) and Head of the Kapuas Regency Office of the Ministry of Religion, Head of the Administrative sub-division, Head of the Islamic Community Guidance section of the Kapuas Regency Office of the Ministry of Religion. The results of this study indicate that: every Islamic Religious Instructor continuously needs to improve the Competence of knowledge, skills, attitudes, and self-development, as well as understand the vision and mission of the Religious Instructor itself.